THE ROLE OF RECITE CULTURE IN FORMING SANTRI BEHAVIOR IN THE TPA SUBULUSSALAM BANDA ACEH - Nisa Khairuni (STAI Al-Washliyah Banda Aceh, 2019)
The formation of behavior in accordance with the national culture is certainly not solely carried out in the family and at school, but also through a series of study activities such as habituation in life though religious behavior, honesty, discipline, tolerance, hard work, peace, and reponsibility. The problem in this paper is, how is the role of recite culture in forming santri behavior in the TPA Subulussalam Banda Aceh? and what are the obstacles encountered in recite culture in the formation the behavior of santri in the TPA Subulussalam Banda Aceh? To answer this problem, this study uses a qualitative approach with a total of 5 people consistinf of the director, 2 ustaz/ah, and 2 santri, data collection was carried out using observation, interviews and documentation techniques. The results of this study indicate that the culture of recite plays an important role forming the behavior of santri, this is because the culture of teaching is assosiated with attitude and norms that are in accordance with religious guidance. The recite culture is applied in TPA Subulussalam Banda Aceh in the form of the asar prayer in congregation, shaking hands with teacher, smiling, speaking politely, closing genitals, reading prayers before learning, tahfīdh, apologize to the teacher at the end of the teaching and learning process. The culture of recite is applied in order to shape the behavior to be better. The obstacles experienced in the application of the recite culture in forming the behavior of santri are influenced by the environment, social media, lack of time for students to recite, and lack of awareness of the santri themselves.